"Or la-goyim": From Diaspora theology to Zionist dogma. Issue 1 (2nd January 2020) - Kaye, Alexander
ABSTRACT: The term "a light unto the nations" is a hallmark of modern Jewish identity but the subtle divergences in the meaning of the expression among its diverse proponents shed light on the continuities and differences among modern Jewish ideologies. David Ben-Gurion, in particular, regarded the calling to be "a light unto the nations" as a central mission of the State of Israel. Before the 1950s, however, almost all Zionists, including Ben-Gurion himself, repudiated the term because they associated it with diasporist ideology. This article explores its shifting meanings in Zionist discourse, with a special focus on Ben-Gurion's rhetoric. It explains Ben-Gurion's changing attitudes term and shows how his innovative uses of the term allowed him to navigate between modernity and traditional Judaism, between Zionism and its opponents, and between the various streams within the Zionist movement. It reminds us that the lexical continuity of figurative terms can mask conceptual fluctuation and enhances a picture of Zionism that acknowledges both its revolutionary novelty and its place in the long continuum of Jewish life.